1999
DOI: 10.1046/j.1365-2796.1999.00418.x
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and leukotrienes: antileukotrienes as novel anti‐asthmatic drugs

Abstract: Abstract. Claesson H-E, Dahlén S-E (Karolinska

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
5

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 241 publications
(344 reference statements)
1
81
0
5
Order By: Relevance
“…It is also possible that differences in the production of and/or response to LTB 4 may contribute to the strain variation seen in the 5LO-dependent component of inflammatory responses. In humans, it has been suggested that increased production of cysteinyl-LT correlates with susceptibility to aspirin-intolerant asthma (37,38). Recent studies have shown that variations in the synthesis of cysteinyl-LT result from a polymorphism in the LTC 4 synthase gene promoter, which causes constitutive overexpression of this enzyme in aspirin-sensitive patients (37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that differences in the production of and/or response to LTB 4 may contribute to the strain variation seen in the 5LO-dependent component of inflammatory responses. In humans, it has been suggested that increased production of cysteinyl-LT correlates with susceptibility to aspirin-intolerant asthma (37,38). Recent studies have shown that variations in the synthesis of cysteinyl-LT result from a polymorphism in the LTC 4 synthase gene promoter, which causes constitutive overexpression of this enzyme in aspirin-sensitive patients (37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that variations in the synthesis of cysteinyl-LT result from a polymorphism in the LTC 4 synthase gene promoter, which causes constitutive overexpression of this enzyme in aspirin-sensitive patients (37)(38)(39)(40). Differing expression levels of LTC 4 synthase may account for variability observed in the response to LT inhibitors used in the treatment of asthma (37).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, LTB 4 is a potent chemotactic and chemokinetic agent that recruits proinflammatory cells towards sites of inflammation [40]. But also tumorigenesis, particularly of colon, breast, prostate, and lung carcinoma has been associated with excessive PGE 2 and LT formation [16,18,19].…”
Section: Page 21 Of 39mentioning
confidence: 99%
“…LTB 4 is a potent chemoattractant for leukocytes causing adherence of phagocytes to vessel walls, neutrophil degranulation and release of superoxide anions, whereas cysLTs are potent bronchoconstrictors increasing vascular permeability and stimulating mucus secretion from airways [5]. These biological actions of LTs are mediated by specific G protein-coupled receptors (GPCRs) on the surface of their target cells.…”
Section: Biological Effects Of Leukotrienesmentioning
confidence: 99%